Designing Game File Compression Applications With Implementing the Stout Code Algorithm - Iqbal, Iqbal (Management of Information System Journal, 2024)
Games today are increasingly modern and have stunning graphics so that the size of the game files contained in the game becomes very large, because these games are increasingly modern and have very stunning graphics so that the graphics are very realistic. Games that are now available on computers or smart phones have stunning graphics and each one must have a game file that is on the storage media. Game files contained in the storage media can cause the capacity of the storage media to reach its limit, and game files on the computer version usually require that the game be downloaded or files that have not been installed, in contrast to the mobile version, in the mobile version the requirements for playing the game must download the application that has been provided to download the game. The problem in this research is that there is a game file whose size is very large so that it will be a problem for storage media and this can cause the performance of devices such as computers or smart phones to become slower. Therefore for the solution in the previous paragraph, namely by using the compression technique. Compression is reducing the size, or in computer science compression is reducing the bit size of the data contained on the storage media so that the capacity space on the storage media is decreasing. The type of compression technique used in this study is lossless. Lossless compression is a compression technique, in which the use of this lossless compression technique, when compressed data is not the same as the data before compression and the data after compression can be decompressed into data like the original before compression. In this study, we will design a special compression application for game files, where game files have a large size so that it can cause the capacity of the storage media to decrease and this can cause performance on devices such as computers or smart phones to slow down. . And in this research, to compress the game file, it will apply an algorithm, namely the stout code algorithm. The stout code algorithm is one of the algorithms related to data compression, and in this study we can see the results of game file compression by applying the stout code algorithm. After doing the compression and decompression process using the stout code algorithm, the application for game file compression that has been designed before can be run, namely by running the application, then press the file search button to find the game file to be compressed, then press the save file button to save the game file will be saved, then press the compression button to compress the game file and the game file is successfully compressed, to decompress do the same thing, find and save the file then press the decompress button and the game file is successfully decompressed